Students’ Perceptions of Quizizz as a Formative Assessment Tool for Reading Comprehension in EFL Learning - Dea Alawiah Amini; Wahyu Satya Gumelar; Riki Ruswandi (Universitas Islam Negeri Palopo, 2025)
The primary purpose of this study was to explore the application of Quizizz as a formative assessment tool in teaching reading comprehension in English as a Foreign Language (EFL) classrooms. This study examines high school students’ perceptions of quizzes as a formative assessment tool for reading comprehension within EFL contexts. It focuses on increasing digital-based learning engagement among high school students. Using a quantitative research design, this study surveyed 58 eleventh-grade students from SMA PGRI 2 Bandung who had experience using Quizizz in reading activities. Data were collected through a validated 27-item questionnaire using a 5-point Likert scale (Cronbach's Alpha = 0.898). The results revealed that the average student response was in the